Prototype Mobile Intra Oral Camera - Rachmawat, Almira; Harijanto, Endanus; Soekartono, R. Helal (International Journal of Psychosocial Rehabilitation, 2020)
Background: Clinical photograph is needed as clinical database, documentation, monitoring, demonstration, and publication. Beside as a dental record, clinical photograph can also enhance patient-doctor communication. Based on a survey from 23 respondents, 18 of them didn’t use oral camera in their clinic, while 5 others use them. Intra oral camera can be used to ease dentist interaction to educate patient effectively. Therefore, a new mobile device is needed. Purpose: To help dentist documented patient’s medical history digitally and to help dentist giving dental education to patient about their oral conditions. Methods: This is an experimental laboratory study to test a prototype that captured the image of oral condition through a questioner with 30 dental student respondents. Data are then analyzed with Spearman correlation test. Result: There’s a significant correlation between the 4 variables, so it can be said that this device can be used to record clinical photograph of patient’s oral condition. Conclusion: The image from the mobile intra oral camera can be use to see the inside of a patient’s mouth and this device is mobile because it can be carried everywhere by dentist easily.